Ação missionária, repartição geográfica e etnicidade na região do Rio Negro - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1998)
The Rio Negro region was an area of strong missionary presence among the Indians between the 17th and 19th centuries. In order to gather information on the migrations, the "descent" of Indian groups and the missionary action in the Rio Negro region during the 18th century, 8 codices and approximately 700 documents were researched in the Public Archives of Pará. The Indians were classified as: registered Indians when they came to serve as slaves; unregistered Indians when there were no interpreters or priests to classify them; condition Indians when they came to work as slaves for a fixed period of five years; unregistered Indians when there was no mention of them in the documents; and free Indians who came as freedmen from 1745 to 1755. There are records of 2,569 Indians who left the Rio Negro and 2,387 as Indians who arrived in Belém, of which 284 came with registration, 1,077 without registration, 408 without reference, 618 as conditioned and 805 as free (they continued working but receiving wages, food and clothing). It is observed that the presence of missionary priests in Rio Negro works as a modifying element of the indigenous habits and customs, promoting the gathering of several previously dispersed groups, making them captive and imposing their religion as the only means of salvation.
Missionary action, geographical distribution and ethnicity in the Rio Negro region
Keywords: Missionários; Indígenas; Colonização; CNPQ::CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL::HISTORIA DO BRASIL COLONIA